PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PT. SINAR NUSRA PRESS UTAMA - Susastra, Putu Widya; Subudi, Made (E-Jurnal Manajemen, 2016)
This study aimed to analyze the influence of transformational leadership on job satisfaction and Organizational Citizenship Behavior (OCB) as well as to analyze the influence of job satisfaction on OCB. This study using   a saturated sampling method with 70 employees. This study was conducted at PT. Sinar Nusra Press Utama. Data were collected using interviews and questionnaires. Data analysis techniques used in this research is the path analysis. The results show that 1) Transformational leadership has direct and positive influence on job satisfaction. 2) Transformational leadership has direct and positive influence on OCB. 3) Employee satisfaction affect indirectly transfortional leadership on OCB. 4) Job satisfation has direct and positive effect toward OCB.   Keywords: Transformational Leadership, job satisfaction, organizational citizenship behavior